KINERJA PEGAWAI DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA KENDARI - Suharman, Mitra Julia; Utha, Arifin; Taufik, Taufik (REZ PUBLICA, 2020)
This study aims to determine and describe the Performance of Employees in Improving the Quality of Public Services at the Investment Office and One Stop Services in the City of Kendari. The method used in this research is descriptive qualitative, which gives a careful depiction of a particular phenomenon from the results of observations, interviews, and documentation studies, so as to be able to describe various matters relating to Employee Performance in Improving Quality of Public Services. The technique used is purposive sampling, which is the technique of determining samples based on the needs for specific purposes. Data collection in this research was carried out through a process of interviews, documentation studies, observations. Then analyzed descriptively qualitatively using the stages of data reduction, data presentation, and drawing conclusions. Based on the results of the study concluded that the Performance of Employees in Improving the Quality of Public Services at the Investment Office can be said to be good, seen from the work performance and achievement of targets that can be seen from the charter, as well as the initiative and satisfaction provided by employees is quite good, for effective services and efficient. Then for service users are satisfied with the services provided to employees in the Office of Investment and PTSP Kendari City, because service users feel valued with employee friendly attitude and are not discriminated against.